Roles of Non-cholinergic Intrapancreatic Nerves, Serotonergic Nerves, on Pancreatic Exocrine Secretion in the Isolated Perfused Rat Pancreas - Jiang, Zheng er (The Korean Physiological Society and The Korean Society of Pharmacology, 2011)
It has been rereported that axons which display 5-hydroxytryptamine (5-HT) immunoreactivity are abundant in the pancreas and the majority of serotonergic axons terminate within intrapancreatic ganglia, islet and acini. This histological result strongly suggests that intrapancreatic serotonergic nerves could affect to the pancreatic endocrine and exocrine secretion. Thus, this study was aimed to investigate whether intrapancreatic serotonergic nerves could affect pancreatic exocrine secretion and an action mechanism of the intrapancreatic serotonergic nerves. The rats were anesthetized with a single injection of urethane. The median line and the abdominal aorta was carefully dissected and cannulated with PE-50 tubing just above the celiac artery, and then tightly ligated just below the superior mesenteric artery. The pancreatic duct was also cannulated with Tygon microbore tubing. With the addition of serotonin, pancreatic volume flow and amylase output were significantly inhibited electrical field stimulation (EFS). On the other hand, pancreatic volume flow and amylase output were significantly elevated in EFS with the addition of spiperone. EFS application, however, pancreatic volume flow and amylase output had no significant change in cholecystokinin (CCK) alone when serotonin was applied under a 5.6 mM glucose background. Pancreatic volume flow and amylase output under 18 mM glucose background were significantly elevated in CCK plus serotonin than in CCK alone. These data suggest that intrapancreatic serotonergic nerves play an inhibitory role in pancreatic exocrine secretion and an important role in the insulin action or release.